PENGARUH PENGGUNAAN MEDIA MAGNETIC BOARD TERHADAP KREATIVITAS SISWA MEMBUAT KOLASE (Studi pada mata pelajaran SBdP kelas IV SDN 17 Bajoe Kecamatan Tanete Riattang Timur Babupaten Bone) - Sitti Rahmi; Achmad Shabir; A.Sulfadila (MACCA : Science-Edu Journal, 2026)
This study is a quantitative research with an experimental method using a pre-experimental design, namely the OGPPD. The purpose of this study is to determine the effect of using magnetic board media on students’ creativity in making collages in the SBdP subject for fourth grade students of SDN 17 Bajoe, Bone Regency. The independent variable in this study is magnetic board media, while the dependent variable is students’ creativity in making collages. The population consists of all fourth grade students totaling 41 students, using a saturated sampling technique. Data were collected using a performance test with a rubric-based assessment sheet. Data analysis was carried out using descriptive and inferential statistics, including normality tests and hypothesis testing. The results show that the average score of students’ creativity before using the magnetic board media was 54.43, , while after using the media it increased to 69.32. The hypothesis test results indicate that the t-value (10.393) is greater than the t-table value (2.02108) with a significance value of 0.000 < 0.05. Therefore, there is a significant effect of using magnetic board media on students’ creativity in making collages.